Online Learning Platform Integration and English Academic Achievement among Secondary School Students - Rexon C. Dunque; Nhelbourne K. Mohammad (Journal of Pedagogy and Education Science, 2026)
The integration of digital technologies has transformed instructional practices in secondary education. Online learning platforms provide interactive environments that support lesson delivery, collaborative learning, and digital assessment. This study examined the extent of online learning platform integration and its influence on the academic achievement of Grade 10 students in English. A descriptive–correlational research design was employed involving 347 students from selected public secondary schools in the Schools Division of Zamboanga del Norte, Philippines. Data were collected using a researcher-developed questionnaire measuring instructional use, learning activities, and assessment and feedback, while students’ academic achievement was obtained from official school records. Descriptive statistics, Pearson correlation, and multiple regression analysis were used to analyze the data. Results revealed that online learning platforms were highly integrated in English instruction (M = 3.77). A moderate positive relationship was found between platform integration and academic achievement (r = 0.46, p < .05). Regression analysis showed that instructional use, learning activities, and assessment and feedback significantly predicted academic achievement, with learning activities emerging as the strongest predictor. The findings suggest that effective integration of online learning platforms can enhance students’ academic performance in English.